2017
DOI: 10.1016/j.asr.2017.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetries in the ionosphere response observed during the high-speed solar wind streams of the 24–28 August 2010

Abstract: This paper presents the geomagnetic and ionospheric responses to a high speed solar wind stream (HSS) impacting the magnetosphere on 24 August 2010. We focus our study on the interhemispheric conjugated behavior. The solar wind speed remained very high during 5 days from 24 to 28 August 2010. By using magnetometer and ground-based GPS data from various approximately conjugated magnetic observatories and GPS stations, we studied the hemispheric asymmetries in the magnetic signature, Vertical Total Electron Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…It showed that the geomagnetic fields at high latitudes oscillated drastically during the storm due to the influence of high-speed solar winds. This is in good consistency with previous discoveries of magnetic responses to high-speed solar winds at high latitudes regions [1,39], leading to ionosphere TEC variations. The asymmetry feature was also found between the northern hemisphere and southern hemisphere.…”
Section: Global Morphology Of Geomagnetic Stormssupporting
confidence: 92%
See 1 more Smart Citation
“…It showed that the geomagnetic fields at high latitudes oscillated drastically during the storm due to the influence of high-speed solar winds. This is in good consistency with previous discoveries of magnetic responses to high-speed solar winds at high latitudes regions [1,39], leading to ionosphere TEC variations. The asymmetry feature was also found between the northern hemisphere and southern hemisphere.…”
Section: Global Morphology Of Geomagnetic Stormssupporting
confidence: 92%
“…where S R (H) denotes the solar daily variation of the earth's magnetic field related to the regular ionospheric dynamo. λ denotes the magnetic dip angle of the given location, D iono represents the magnetic disturbance due to the disturbed ionosphere electric currents, H SYM represents SYM-H, the contributions of the electric currents in the magnetosphere (refer to Reference [1]).…”
Section: Calculation Of Geomagnetic Perturbationsmentioning
confidence: 99%
“… D iono can be estimated using the following expression (Le Huy & Amory‐Mazaudier, ; Zaourar et al, ): Diono=normalΔHSYMH·cosϕitalicSq where ΔH is the variation of H component obtained using , SYM − H is the estimation of the ring current and ϕ is the geomagnetic latitude. It is worth noting that D iono can be used to estimate ionospheric electric currents only on the dayside where they circulate.…”
Section: Data Set and Data Processingmentioning
confidence: 99%
“…In equation (3), STEC is in TECU with 1 TECU = 10 16 electrons/m 3 , t k À t k À 1 is the time difference between successive epoch = 30 s. ROT is converted in TECU/min by multiplying by 60 s (Azzouzi et al, 2015;Zaourar et al, 2017).…”
Section: Space Weathermentioning
confidence: 99%